Local factors mediate the response of biodiversity to land use on two African mountains. (28th December 2016) - Jung, M.; Hill, S. L. L.; Platts, P. J.; Marchant, R.; Siebert, S.; Fournier, A.; Munyekenye, F. B.; Purvis, A.; Burgess, N. D.; Newbold, T.
Abstract: Land‐use change is the single biggest driver of biodiversity loss in the tropics. Biodiversity models can be useful tools to inform policymakers and conservationists of the likely response of species to anthropogenic pressures, including land‐use change. However, such models generalize biodiversity responses across wide areas and many taxa, potentially missing important characteristics of particular sites or clades. Comparisons of biodiversity models with independently collected field data can help us understand the local factors that mediate broad‐scale responses. We collected independent bird occurrence and abundance data along two elevational transects in Mount Kilimanjaro, Tanzania and the Taita Hills, Kenya. We estimated the local response to land use and compared our estimates with modelled local responses based on a large database of many different taxa across Africa. To identify the local factors mediating responses to land use, we compared environmental and species assemblage information between sites in the independent and African‐wide datasets. Bird species richness and abundance responses to land use in the independent data followed similar trends as suggested by the African‐wide biodiversity model, however the land‐use classification was too coarse to capture fully the variability introduced by local agricultural management practices. A comparison of assemblage characteristics showed that the sites on Kilimanjaro and the Taita Hills had higher proportions of forest specialists in croplands compared to the Africa‐wide average. Local human population density, forest cover and vegetation greenness also differed significantly between the independent and Africa‐wide datasets. Biodiversity models including those variables performed better, particularly in croplands, but still could not accurately predict the magnitude of local species responses to most land uses, probably because local features of the land management are still missed. Overall, our study demonstrates that local factors mediate biodiversity responses to land use and cautions against applying biodiversity models to local contexts without prior knowledge of which factors are locally relevant. Abstract : Biodiversity models can be useful tools to predict species responses to human land use, yet they often generalize over many local factors in order to be broadly applicable. We compared estimates from an African‐wide biodiversity model with new independent data. Our results show that overall biodiversity responds similarly to land use in both datasets, yet we found that certain factors of local land‐use systems can lead to mismatches if they do not conform to African‐wide averages. We make recommendations about additional factors to include in biodiversity models and their use in new local contexts.